2014
DOI: 10.4049/jimmunol.1301611
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effect of IVIG on Inflammatory Arthritis in Mice Is Dependent on the Fc Portion and Independent of Sialylation or Basophils

Abstract: High-dose i.v. Ig (IVIG) is used to treat various autoimmune and inflammatory diseases; however, the mechanism of action remains unclear. Based on the K/BxN serum transfer arthritis model in mice, IVIG suppression of inflammation has been attributed to a mechanism involving basophils and the binding of highly sialylated IgG Fc to DC-SIGN–expressing myeloid cells. The requirement for sialylation was examined in the collagen Ab-induced arthritis (CAbIA) and K/BxN serum transfer arthritis models in mice. High-dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
104
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 119 publications
(116 citation statements)
references
References 56 publications
9
104
3
Order By: Relevance
“…Despite this convincing evidence, some studies using different or identical in vivo model systems showed sialic acid-independent pathways of IVIg activity (28,29). However, none of these studies can be compared directly because of the use of different protocols and experimental conditions.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Despite this convincing evidence, some studies using different or identical in vivo model systems showed sialic acid-independent pathways of IVIg activity (28,29). However, none of these studies can be compared directly because of the use of different protocols and experimental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…However, none of these studies can be compared directly because of the use of different protocols and experimental conditions. For example, the use of desialylated IVIg generated with unqualified desialylation processes (potentially leading to IVIg preparations with residual sialylation content) or alteration to the composition of the IVIg mixture during desialylation or purification could potentially explain the lack of requirement of sialylation in the model of inflammatory arthritis (28,29). Additionally, some studies comparing the biological activity of IVIg and desialylated IVIg used fairly high doses outside the linear range of dose-response, which complicates interpretation of the results because of the complex and multiple mechanisms of IVIg (29).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations